Endothelial basement membrane laminin 511 is essential for shear stress response. (15th May 2017) - Di Russo, Jacopo; Luik, Anna‐Liisa; Yousif, Lema; Budny, Sigmund; Oberleithner, Hans; Hofschröer, Verena; Klingauf, Juergen; van Bavel, Ed; Bakker, Erik NTP; Hellstrand, Per; Bhattachariya, Anirban; Albinsson, Sebastian; et al.
Abstract :